Analyzing animal societies : quantitative methods for vertebrate social analysis - Whitehead, Hal (University of Chicago Press, 2008)
Animals lead rich social lives. They care for one another, compete for resources, and mate. Within a society, social relationships may be simple or complex and usually vary considerably, both between different groups of individuals and over time. These social systems are fundamental to biological organization, and animal societies are central to studies of behavioral and evolutionary biology. But how do we study animal societies? How do we take observations of animals fighting, grooming, or forming groups and produce a realistic description or model of their societies?. Analyzing Animal Societ.